2019
DOI: 10.17660/actahortic.2019.1232.32
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of garden roses to cercospora leaf spot

Abstract: Cercospora rosicola is a fungal pathogen that attacks roses and causes spotting on leaves, chlorosis and in severe cases, defoliation. This disease has become more prominent in roses after the widespread use of black spot resistant roses, most likely due to the reduction of fungicide applications on roses. The objective of this thesis is to evaluate garden roses and identify QTLs for resistance to cercospora leaf spot disease. Identification of susceptible and resistant roses to cercospora leaf spot is the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 47 publications
6
5
0
Order By: Relevance
“…The conidia were observed under microscope as cylindrical and having septa ( Figure 26) ( Table 3). The results were in conformity with the study of Kang et al (2019). Figure 27).…”
Section: Rosesupporting
confidence: 92%
“…The conidia were observed under microscope as cylindrical and having septa ( Figure 26) ( Table 3). The results were in conformity with the study of Kang et al (2019). Figure 27).…”
Section: Rosesupporting
confidence: 92%
“…In this study, CLS showed low to moderately high h 2 and moderately high H 2 , as previously reported (Kang et al, 2019). The G×E/G ratios (1.33 to 2.33) and GGE biplots indicated that rose genotypes exhibited different patterns of CLS incidence in different environments (location and/or month/year).…”
Section: Heritability and G×esupporting
confidence: 88%
“…Using PBA and two diploid rose multiparent populations, 38 QTLs distributed over the seven LGs were identified for CLS resistance, consistent with reports indicating that CLS resistance is polygenic in rose (Kang et al, 2019). Three large-effect QTLs associated with CLS resistance in each population were consistently detected with decisive evidence in most data sets on LGs 3, 4, and 6.…”
Section: Qtl Detectionsupporting
confidence: 82%
See 2 more Smart Citations